Tomographic control of sindesmosis reduction after surgical fixation - Castro, Allex Amaral; Pansini, José Vicente; Martins, Elicimar Beltran; Castro, Adham Amaral; Nunes, Eduardo Kaiser Ururahy (Scientific Journal of the Foot & Ankle, 2018)
Objective: To determine percentages of types A (flat) and B (concave) of the distal tibiofibular joint in patients with ankle fractures or chronic ligament instabilities, with syndesmosis lesions; check the shape of the fixation and position of the fibula in this joint; to identify poor fibular reduction and its frequency in types A and B; patients according to the AOFAS criteria. Methods: 104 patients surgically treated with syndesmosis fixation underwent clinical evaluation using AOFAS functional criteria and tomographic exams to classify the distal tibiofibular joint in types A or B and evaluated the poor position of the fibula in this joint. Results: Distal tibiofibular joint type A was present in 27 ankles and type B in 77. Non-anatomical reduction of the fibula (17 ankles) was more frequent in type A than in type B and more frequent in fractures than in instabilities. The AOFAS score was 91.79 points in the 87 patients with good reduction and 86.76 points in the 17 patients with poor fibula reduction. Conclusion: Distal tibiofibular joint type B was more frequent than type A (p=0.00001); there was poor reduction of the fibula in this joint in 17 ankles (16.34%). Poor fibula reduction was more frequent in fractures than in instabilities (p=0.006). The poor reduction was more constant in type A than in type B, without statistical significance (p=0.34). The AOFAS score was 91.79 points in patients with good reduction and 86.76 points in patients with poor fibula reduction in the distal tibiofibular joint. Level of Evidence IV; Therapeutic Studies; Case Series.